The Influence of Small-Sided Games and Floaters Intervention on Physical Components of Soccer Players - Midhun Kumar MA; Vinod Kumar G; Vinu W (Physical Education Theory and Methodology)
Background. In soccer, numerical superiority enhances the effectiveness of both offensive and defensive actions performed by players. To improve the performance of the players, small-sided games (SSGs) with numerical inferiority and superiority should be incorporated into training sessions. Objectives. The study aimed to evaluate the effect of a 12-week training program using floaters and small-sided games (SSGs) on the physical performance of soccer players.